2016
DOI: 10.1371/journal.ppat.1005738
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus NS1 Disrupts the Endothelial Glycocalyx, Leading to Hyperpermeability

Abstract: Dengue is the most prevalent arboviral disease in humans and a major public health problem worldwide. Systemic plasma leakage, leading to hypovolemic shock and potentially fatal complications, is a critical determinant of dengue severity. Recently, we and others described a novel pathogenic effect of secreted dengue virus (DENV) non-structural protein 1 (NS1) in triggering hyperpermeability of human endothelial cells in vitro and systemic vascular leakage in vivo. NS1 was shown to activate toll-like receptor 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
344
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 286 publications
(364 citation statements)
references
References 56 publications
16
344
1
3
Order By: Relevance
“…142 NS1 was also shown to induce hyperpermeability in human endothelial cell monolayers independent of cytokines via disruption of the glycocalyx layer that lines the endothelium. 143 These findings identify new potential targets for dengue therapeutics and support inclusion of NS1 in dengue vaccines.…”
Section: Pathogenesismentioning
confidence: 74%
“…142 NS1 was also shown to induce hyperpermeability in human endothelial cell monolayers independent of cytokines via disruption of the glycocalyx layer that lines the endothelium. 143 These findings identify new potential targets for dengue therapeutics and support inclusion of NS1 in dengue vaccines.…”
Section: Pathogenesismentioning
confidence: 74%
“…Processing and activation of heparanase occur after proteolytic processing by cathepsin L, a characteristic lysosomal cysteine proteinase of the papain superfamily of peptidases that is implicated in multiple physiological and pathological processes (23)(24)(25). To investigate whether PRRSV infection activates heparanase via cathepsin L, cathepsin L activity in Marc-145 cells was initially assessed at various times or MOIs after PRRSV infection using a Magic Red cathepsin L detection kit.…”
Section: Resultsmentioning
confidence: 99%
“…Since HS is used by many viruses for initial attachment to target cells, it is reasonable to assume that heparanase might be involved in the pathogenesis of other viruses as well. It has been reported that dengue virus nonstructural protein 1 (NS1) disrupts the endothelial glycocalyx layer on human pulmonary microvascular endothelial cells by NS1-induced expression of sialidases and heparanase (23). Furthermore, heparanase is upregulated in numerous human diseases such as cancer, diabetes, renal disease, and Alzheimer's disease (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DHF had both the lowest platelet count and highest aPTT on day 5, which might render them the most likely to have bleeding episodes after day 5 [1]. However, bleeding episodes depend on several factors, including vasculopathy, thrombocytopenia, platelet capacity, prothrombin-complex deficiency, and dengue viral NS1 protein [46]. Experimental ex vivo investigations revealed that platelets upon exposure to DENV enhanced the capacity of engulfment by monocytes, which altered the phenotypes toward macrophages or dendritic-like cells after the phagocytosis of the DENV-activated platelets.…”
Section: Discussionmentioning
confidence: 99%